2022
DOI: 10.3390/nu14050964
|View full text |Cite
|
Sign up to set email alerts
|

Black Sea Mussels Qualitative and Quantitative Chemical Analysis: Nutritional Benefits and Possible Risks through Consumption

Abstract: Mussels have a particular nutritional value, representing a highly valued food source and thus sought after worldwide. Their meat is a real culinary delicacy, rich in proteins, lipids, carbohydrates, trace elements, enzymes, and vitamins. The seasonal variation of mussels’ biochemical composition has been studied to determine the best harvesting period to capitalize on various biologically active fractions. In this work biochemical determinations have been performed on fresh flesh samples of Mytilus galloprovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Our study indicated the low-to-moderate HM contamination of mussels at all sampling sites. The results agreed with previous studies carried out along the Romanian Black Sea coast [ 31 , 35 , 41 ]. The HM levels found in our study were similar to those from the Turkish Black Sea coast [ 35 ] and Baltic Sea [ 9 ], higher than those from the southeastern Adriatic Sea [ 1 ], and relatively low compared with the results of other studies carried out in the Gulf of Biscay [ 37 ] and Mediterranean Sea [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study indicated the low-to-moderate HM contamination of mussels at all sampling sites. The results agreed with previous studies carried out along the Romanian Black Sea coast [ 31 , 35 , 41 ]. The HM levels found in our study were similar to those from the Turkish Black Sea coast [ 35 ] and Baltic Sea [ 9 ], higher than those from the southeastern Adriatic Sea [ 1 ], and relatively low compared with the results of other studies carried out in the Gulf of Biscay [ 37 ] and Mediterranean Sea [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, trophic transfer, also known as bioaccumulation, exposes humans to chemicals released by microplastics indirectly. More precisely, these chemicals are compounds that enter into the composition of microplastics or persistent pollutants adsorbed by them (pesticides, toxic metals) [ 155 , 156 , 157 , 158 , 159 ]. These chemicals accumulate in the body from multiple sources.…”
Section: Potential Effects Of Microplastics On Human and Animal Healthmentioning
confidence: 99%
“…Polluted marine areas for harvesting seafood or fish should also be avoided [26][27][28]. Eating contaminated food can seriously affect health [29][30][31]. In addition, it is essential to avoid excessive administration of drugs or their consumption without the supervision of a specialist [32,33] due to their potential toxicity.…”
Section: Introductionmentioning
confidence: 99%